2021
DOI: 10.1590/1983-1447.2021.20200396
|View full text |Cite
|
Sign up to set email alerts
|

Laser in wounds: knowledge translation to an effective and innovative nursing practice

Abstract: Objective To describe the knowledge translation obtained through research of low-level laser therapy to wound treatment in the clinical practice. Methods Experience report about implementation strategies of this new technology in a university hospital, being an extension course the main one, developed between May and December 2019. Results The course was carried out by researchers in partnership with clinical nurses to 13 nurses from different areas with previous experience in wound care. Were taught 30 theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
5
0
3
Order By: Relevance
“…Advanced practice nursing in combination with laser therapy represents a promising approach to improving health care (11) . The ability of nurses to assess, prescribe, and administer laser therapy treatments can lead to positive outcomes for a wide range of clinical conditions (12)(13) . Therefore, this study is a tool to generate knowledge and substantiate advanced nursing interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced practice nursing in combination with laser therapy represents a promising approach to improving health care (11) . The ability of nurses to assess, prescribe, and administer laser therapy treatments can lead to positive outcomes for a wide range of clinical conditions (12)(13) . Therefore, this study is a tool to generate knowledge and substantiate advanced nursing interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Sua aplicação na prática clínica deve ser realizada pelo enfermeiro devidamente habilitado, buscando uma assistência segura ao cliente, baseada em evidências. O cuidado com as feridas deve ser embasado em protocolos adequados e realizados por profissionais com conhecimento técnico e científico (Conselho Federal de Enfermagem, 2018; Conselho Regional de Enfermagem, 2014;De Oliveira Bernardes & Regina Jurado, 2018;Lucena et al, 2021;Oliveira et al, 2018).…”
Section: Introductionunclassified
“…Recent investigations on the care of PIs in individuals assisted in outpatient care, showed that adjuvant LLLT had significant results (7,(10)(11)(12) . This evidence motivated the authors of this article to expand the use of this technology in patients affected by pressure injuries after prolonged hospitalization for the treatment of COVID-19 I, in an outpatient follow-up, in order to obtain better results.…”
Section: Introductionmentioning
confidence: 99%